Preference of using wood and wood products in the construction industry in Peninsular Malaysia - Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Wen, Cheng Ng; Cellathurai, Mutthiah; Khoon, Ark Chin; Senin, Abdul Latib; Lim, Choon Liat (North Carolina State University, 2018)
The objective of this study was to determine the preferences of architects for wood and wood products for specific applications and to assess the attributes that influenced its utilization in the construction sector in Peninsular Malaysia. A questionnaire survey was conducted among 500 practicing architects throughout Peninsular Malaysia, with a response of 27%. The application of wood and wood products by architects was focused primarily on non-structural applications rather than structural applications. It was found that cost, customer demand, durability, natural beauty, availability, ease of design, and workability were primary considerations for architects in specifying wood and wood products in building construction. A factor analysis of the results showed that building regulations, material quality and beauty, customer demand, and design and assembly were the primary determinants that influence architects specifying and using wood and wood products in building construction. It was apparent that the use of wood and wood products in building construction in Peninsular Malaysia has the potential to be further increased through advertising and marketing in the material among the general public, as well as architects and specifiers.